Implementasi Model Pembelajaran Aktif Kreatif Efektif dan Menyenangkan Pada Mata Pelajaran Teknologi Informasi dan Komputer Di SMK N 1 Ampek Angkek - Indah Indria Sari; Supriadi Supriadi; Khairuddin Khairuddin; Riri Okra (Pusat Riset dan Inovasi Nasional, 2023)
This research is motivated by the importance of implementing an effective and fun creative active learning model in class X SMK N 1 Ampek Angkek. Various questions are raised with learning that is still far from the criteria of being active, creative, effective, and fun. This can also be seen from the learning which is still centered on the teacher and students are still busy listening to the lesson. Then the teacher also does not optimize the potential that exists in students. The type of research used is Quasi Experimental Design. The population in this study were class X students of SMK N 1 Ampek Angkek for the 2020/2021 Academic Year. Sampling was carried out using the Nonprobability Sampling technique, namely by taking non-random samples. The first sample consisted of 25 students in the experimental class using the PAKEM model and the second sample consisted of 23 students in the control class using the conventional learning model. The research data was obtained by giving student responses as many as 22 items that have been tested. Based on the results obtained from the mean of the experimental class is 71.76 and the control class is 71.52. The results of the hypothesis using the t-test at a significance level of 0.05 obtained a Sig (2-tailed) of 0.041. So that H0 is rejected and H1 is accepted because 0.041 <0.05. This shows that there is a significant difference between the application of effective and fun creative active learning models in information technology and computer subjects with conventional learning models.